2005
DOI: 10.1002/mabi.200400212
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Water Incorporated in Sulfobetaine Polymer Films as Studied by ATR‐FTIR

Abstract: The structure and hydrogen bonding of water in the vicinity of a thin film of a sulfobetaine copolymer (poly[(N,N-dimethyl-N-(3-sulfopropyl)-3'-methacrylamidopropanaminium inner salt)-ran-(butyl methacrylate)], poly(SPB-r-BMA)), were analyzed with band shapes of O-H stretching of attenuated total reflection infrared (ATR-IR) spectra. The copolymer could be cast as a thin film, of approximate thickness 10 microm, on a ZnSe crystal for the ATR-IR spectroscopy. At an early stage of sorption of water into the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 53 publications
6
118
0
Order By: Relevance
“…[32,43,58,59] The ''graft-to'' method involves (i) the preparation of polymers containing nonfouling and adhesive groups, such as 3,4-dihydroxyphenylalanine (DOPA) groups [24,60] and polylysine segments, [61] and (ii) the direct attachment of the polymers onto the surface. pSB and pCB have been grafted to or from surfaces via several common adhesive linkers, including thiols for a gold surface, [43,45,47,50,51,62,63] silanes for a glass surface, [64] hydrophobic moieties for a hydrophobic surface, [41,65,66] or DOPA for various surfaces, [67,68] or via interpenetrating networks (IPNs) into polyurethane (SPU) matrices. [69] pSB-based hydrogels have also been prepared.…”
Section: Ultralow Fouling Psb and Pcb Zwitterionic Materialsmentioning
confidence: 99%
“…[32,43,58,59] The ''graft-to'' method involves (i) the preparation of polymers containing nonfouling and adhesive groups, such as 3,4-dihydroxyphenylalanine (DOPA) groups [24,60] and polylysine segments, [61] and (ii) the direct attachment of the polymers onto the surface. pSB and pCB have been grafted to or from surfaces via several common adhesive linkers, including thiols for a gold surface, [43,45,47,50,51,62,63] silanes for a glass surface, [64] hydrophobic moieties for a hydrophobic surface, [41,65,66] or DOPA for various surfaces, [67,68] or via interpenetrating networks (IPNs) into polyurethane (SPU) matrices. [69] pSB-based hydrogels have also been prepared.…”
Section: Ultralow Fouling Psb and Pcb Zwitterionic Materialsmentioning
confidence: 99%
“…[49] As mentioned in the Introduction, we have also found by FT-IR and Raman spectroscopies that the hydrogen-bonded network structure of water in the vicinity of zwitterionic polymers was not greatly different from that of pure water. [23][24][25][26][27] Small perturbation of the structure of water primarily hydrating zwitterionic polymer materials has also been reported, [50] and this indicates that the hydration layer at the surface of a zwitterionic polymer might not be so thick. Therefore, we speculate that the hydration layer around a protein molecule that is approaching the surface of zwitterionic polymer collides with the relatively thin hydration layer on the polymer.…”
Section: Complement Activation and Formation Of Tat Complexmentioning
confidence: 99%
“…[21,22] The solution behavior of zwitterionic polymers is often opposite to that of typical polyelectrolytes, exhibiting ''anti-polyelectrolyte'' behavior. Using Raman and IR spectroscopies, we have found that the hydrogen-bonded network structure of water in the vicinity of zwitterionic polymers (phosphobetaine, sulfobetaine and carboxybetaine polymers) was not greatly disturbed, [23][24][25][26][27] suggesting that the small perturbation effect of zwitterionic polymers on the structure of water at polymer-water interfaces is crucial for the biocompatibility of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…15) Platelet adhesion and complement activation on the polymer surface of poly(CMB-r-BMA) showed a minimum value around 30% of the mole ratio of CMB. Polymers containing zwitterionic moieties such as 2-methacryloyloxyethylphosphorylcholine (MPC) 16) and 3-sulfo-N,N-dimethyl-N-3Ј-methacrylamidopropylpropanaminium inner salt (SPB) 17) also have excellent blood compatibility.…”
mentioning
confidence: 99%